My Secret unicorn moonlight journey - Chapman, Linda (London : Puffin, 2007)
When shadow falls ill with a mu-ystery virus, not even Twilight's healing magic seems to help. Lauren and Twilight have to make dangerous journey to the magical land of Arcadia to find a cure, but will they be in time to save him?
Keywords: Ilness -- Fiction; journey -- Fiction; Magic -- Fiction